Researching, disseminating, teaching: obstacles and resources for the study of recent history - Hernández Sánchez, Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In their daily endeavor, the historian who invests in the History of the Present as their field of study finds both impediments and new possibilities in their way. The first obstacle is the peculiar nature of this chronological phase. The classical divisions of history -prehistory, ancient, medieval and modern-are closed off and their incidence in the current sociopolitical reality is quite blurred. However, contemporary history is still open and, within it, is the history of the present, that of the last three living generations. Another drawback is that the sources of the history of the present, although they exist in abundance, are under legal restrictions of access. This makes the task of the researcher, the disseminator, and the teacher more difficult, although the modern digitalization and network dissemination techniques have opened up a broad field of action. Digitalization and access to information on the internet are providing researchers, teachers, and students with new possibilities that, along with the exercising of a critical paradigm, may contribute to writing history from a renewed social and political viewpoint.